Foreign Direct Investment and the Sourcing of Technological Advantage: Evidence from the Biotechnology Industry - Shan, Weijian; Song, Jaeyong (Journal of International Business Studies, 1997)
This paper investigates the proposition that foreign direct investment in a high-technology industry is motivated in part by the sourcing of country-specific technological advantages embedded in foreign firms. The empirical findings show that foreign equity investment is drawn to American biotechnology firms with high levels of patent activity. We suggest that, in the biotechnology industry, foreign direct investment in the form of equity participation can be an efficient vehicle for tapping into country-specific, firm-embodied technological advantages.